2015
DOI: 10.1002/anie.201412307
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenative Homocoupling of Terminal Alkenes on Copper Surfaces: A Route to Dienes

Abstract: Homocouplings of hydrocarbon groups including alkynyl (sp(1) ), alkyl (sp(3) ), and aryl (sp(2) ) have recently been investigated on surfaces with the interest of fabricating novel carbon nanostructures/nanomaterials and getting fundamental understanding. Investigated herein is the on-surface homocoupling of an alkenyl group which is the last elementary unit of hydrocarbons. Through real-space direct visualization (scanning tunneling microscopy imaging) and density functional theory calculations, the two termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 33 publications
2
61
0
2
Order By: Relevance
“…Along with on‐surface arene C−H activation the group of Xu also investigated on‐surface dehydrogenative homocoupling of alkenes and showed that 4‐vinylbiphenyl (VBP) can be dimerized via covalent C−C bond formation at the vinylic position . A Cu(110) crystal was chosen as a carrier at a reaction temperature of 152 °C.…”
Section: On‐surface C−h Activation Reactions For C−c Bond Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with on‐surface arene C−H activation the group of Xu also investigated on‐surface dehydrogenative homocoupling of alkenes and showed that 4‐vinylbiphenyl (VBP) can be dimerized via covalent C−C bond formation at the vinylic position . A Cu(110) crystal was chosen as a carrier at a reaction temperature of 152 °C.…”
Section: On‐surface C−h Activation Reactions For C−c Bond Formationmentioning
confidence: 99%
“… Dimerization of VBP molecules at the terminal vinylic position via on‐surface C−H activation . (Adapted with permission from ref.…”
Section: On‐surface C−h Activation Reactions For C−c Bond Formationmentioning
confidence: 99%
“…Among others, the atomically precise synthesis of carbon nanostructures such as graphene nanoribbons [23][24][25][26][27][28][29][30] and other hydrocarbons like alkanes, dienes and diynes has become a hot topic within the field of onsurface synthesis. [31][32][33][34][35] In particular, it has been demonstrated that the thermally-induced dehalogenation of pre-defined C−X groups (X stands for halogens) provides an efficient route to produce radicals for subsequent C−C couplings on surfaces. 14,24,27 Besides, some reactive intermediates, like arynes, 36 aromatic diradicals and a highly strained ten-membered diyne 37 have been artificially generated on surfaces by cleaving C−X bonds with the aid of STM manipulations and thereby, yielding radicals.…”
mentioning
confidence: 99%
“…In addition, debrominated homocoupling of terminal alkanes, that is, the on‐surface Wurtz reaction, was also reported by our group very recently . Moreover, carbon–carbon coupling through direct C−H activation of hydrocarbons involving different hybridized carbon centers has also been reported as an alternative route . In this manner, linear alkane polymerization, which is of particular scientific and industrial interest, has been achieved on an Au(110) surface where the growth of polymerized alkyl chains is confined in the (1×3) reconstruction grooves of Au(110) .…”
Section: Figurementioning
confidence: 99%
“…In conclusion, through high‐resolution UHV‐STM imaging and DFT calculations, we have demonstrated the dehydrogenative homocoupling of alkyl chains on the Cu(110) surface. In comparison to the reconstructed Au(110) surface, a step‐by‐step reaction pathway from the intact molecules, via the dehydrogenative intermediates, to the final diverse coupling products was observed on Cu(110), whereas the homocouplings of alkene and alkyne molecules were proposed to follow a different pathway . In comparison to the selectively dehydrogenative coupling of quaterphenyl molecules, there is no preferential C site with respect to C−H activation of alkyl chains on Cu(110), which results in the formation of diverse coupling products of alkane molecules on Cu(110).…”
Section: Figurementioning
confidence: 99%